Diatom silicon isotope record of the sediment short core EN18232-1, Lake Khamra, Siberia - Amelie Stieg; Boris K Biskaborn; Ulrike Herzschuh; Andreas Marent; Mikaela Weiner; Dorothee Wilhelms-Dick; Hanno Meyer (PANGAEA, 2025)
This data set is an extension to the previously published data in a bundled publication (Stieg et al., 2024a) from the Russian Lake Khamra (59.99°N, 112.98°E, 340 m a.s.l.), located in eastern Siberia in SW Yakutia. The short core (EN18232-1) was retrieved in summer 2018 and subsampled in 2021 in 39 continuous 1 cm increments covering the last 220 years (ca. 2015-1790 CE). Detailed information about the age-depth model of the short core EN18232-1 can be found in the research paper (Stieg et al., 2024b). We provide diatom silicon isotope values of all 39 samples of the short core EN18232-1, determined from the same aliquots as the diatom oxygen isotope measurements published in an earlier data set (Stieg et al., 2024c). Details of the methods used can be found in Stieg et al. (in process). In general, the laser fluorination method was applied using bromine pentafluoride (BrF5) as a reagent. In several steps the silicon is separated and trapped as silicon tetrafluoride (SiF4) for the subsequent silicon isotope analysis (Chapligin et al., 2010; Maier et al., 2013). The samples were measured on a MAT 252 IRMS at AWI Bremerhaven against a reference gas with known isotopic composition, calibrated to the reference quartz standard NBS-28. The results are expressed as delta notation δ30Si (30Si / 28Si) in per mill ( extperthousand). Analytical precision was better than 0.07 extperthousand (1σ of δ30Si). The dataset includes a weighted mean value for each sample, the standard deviation, and the number of replicates.